Implementation and Evaluation of an Electronic Maternal Early Warning Trigger Tool to Reduce Maternal Morbidity - Blumenthal, Elizabeth A.; Hooshvar, Nina; Tancioco, Virginia; Newman, Rachel; Senderoff, Dana; McNulty, Jennifer (American Journal of Perinatology, 2020)
Objective We compare maternal morbidity and clinical care metrics before and after the electronic implementation of a maternal early warning trigger (MEWT) tool.Study Design This is a study of maternal morbidity and clinical care within three linked hospitals comparing 1 year before and after electronic MEWT implementation. We compare severe maternal morbidity overall as well as within the subcategories of hemorrhage, hypertension, cardiopulmonary, and sepsis in addition to relevant process metrics in each category. We describe the MEWT trigger rate in addition to MEWT sensitivity and specificity for morbidity overall and by morbidity type.Results The morbidity rate ratio increased from 1.6 per 100 deliveries in the pre-MEWT period to 2.06 per 100 deliveries in the post-MEWT period (incidence rate ratio = 1.28, p = 0.018); however, in cases of septic morbidity, time to appropriate antibiotics decreased (pre-MEWT: 1.87 hours [1.11–2.63] vs. post-MEWT: 0.75 hours [0.31–1.19], p = 0.036) and in cases of hypertensive morbidity, the proportion of cases treated with appropriate antihypertensive medication within 60 minutes improved (pre-MEWT: 62% vs. post-MEWT: 83%, p = 0.040). The MEWT trigger rate was 2.3%, ranging from 0.8% in the less acute centers to 2.9% in our tertiary center. The MEWT sensitivity for morbidity overall was 50%; detection of hemorrhage morbidity was lowest (30%); however, it ranged between 69% for septic morbidity, 74% for cardiopulmonary morbidity, and 82% for cases of hypertensive morbidity.Conclusion Overall, maternal morbidity did not decrease after implementation of the MEWT system; however, important clinical metrics such as time to antibiotics and antihypertensive care improved. We suspect increased morbidity was related to annual variation and unexpected lower morbidity in the pre-MEWT comparison year. Because MEWT sensitivity for hemorrhage was low, and because hemorrhage dominates administrative metrics of morbidity, process metrics around sepsis, hypertension, and cardiopulmonary morbidity are important to track as markers of MEWT efficacy.Key Points
Keywords: maternal early warning trigger tool; maternal early warning system; maternal morbidity; maternal mortality